Hearing Loss as the Main Clinical Presentation in NLRP3-Associated Autoinflammatory Disease - Oziębło, Dominika; Leja, Marcin L.; Jeznach, Aldona; Orzechowska, Magdalena; Skirecki, Tomasz; Więsik-Szewczyk, Ewa; Furmanek, Mariusz; Bałdyga, Natalia; Skarżyński, Henryk; Ołdak, Monika (Frontiers in Immunology, 2022)
The NLRP3 gene mutations are the cause of autosomal dominant autoinflammatory disorders (NLRP3-AID). Recently, hearing loss (HL) has been found to be the sole or major manifestation of NLRP3-AID. Here, we tested 110 autosomal dominant HL families with a custom panel of 273 HL genes and found one family carrying the NLRP3 c.1872C>G, p.Ser624Arg mutation. Functional studies revealed that this novel variant is a gain of function mutation, leading to increased activity of caspase-1 and subsequent oversecretion of proinflammatory interleukin-1β. Clinical reanalysis of the affected individuals together with serological evidence of inflammation and pathological cochlear enhancement on FLAIR-MRI images, guided our diagnosis to atypical NLRP3-AID. The study highlights the role of genetic analysis in patients with progressive postlingual HL. This can help to identify individuals with hereditary HL as a consequence of NLRP3-AID and allow timely and effective treatment with interleukin-1-receptor antagonist.